One Health at Risk: Plasmid-Mediated Spread of mcr-1 Across Clinical, Agricultural, and Environmental Ecosystems - Abdelaziz Touati; Nasir Adam Ibrahim; Assia Mairi; Hassina Kirat; Nosiba S. Basher; Takfarinas Idres (Antibiotics)
The global dissemination of plasmid-mediated mcr genes, which confer resistance to the last-resort antibiotic colistin, represents a critical public health challenge driven by the interplay of clinical, agricultural, and environmental factors. This review examines the genetic and ecological dynamics of mcr-bearing plasmids, focusing on their role in disseminating colistin resistance across diverse bacterial hosts and ecosystems. Key plasmid families demonstrate distinct evolutionary strategies, including IncI2, IncHI2, and IncX4. IncI2 plasmids favor stability in livestock and clinical settings. IncHI2 plasmids, on the other hand, leverage transposons to co-select for multidrug resistance, while IncX4 plasmids achieve global dissemination through streamlined, conjugation-efficient architectures. The pervasive spread of mcr genes is exacerbated by their integration into chromosomes via mobile genetic elements and co-selection with resistance to other antibiotic classes, amplifying multidrug-resistant phenotypes. Environmental reservoirs, food chains, and anthropogenic practices further facilitate cross-niche transmission, underscoring the interconnectedness of resistance under the One Health framework. Addressing this crisis requires coordinated strategies, including reducing colistin misuse in agriculture, enhancing surveillance of high-risk plasmid types, and fostering international collaboration to preserve antimicrobial efficacy and mitigate the threat of untreatable infections.